2022
DOI: 10.2478/jee-2022-0058
|View full text |Cite
|
Sign up to set email alerts
|

A fundamental approach: E-polarized electromagnetic wave diffraction by two dimensional arbitrary-shaped objects with impedance boundary condition

Abstract: In the present study, a new methodology in computational electromagnetics is developed for two-dimensional arbitrarily-shaped objects with impedance boundary conditions. The proposed approach investigates the E-polarized electromagnetic diffraction by a two-dimensional object with the Leontovich boundary condition. The scattered electric and magnetic fields are expressed as the convolution integral of the corresponding Green’s function and the current induced on the obstacle surface. After obtaining integral e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This approach eliminates the singularity problems in radiation integrals. In the regularized form of MAS, Hankel's function (Green's function in 2D problems) is regularized and singularity problems are solved by regularizing the kernel of the radiation integrals (Hankel's function) [19]. For smooth surfaces, MAS gives better results, whereas the regularized form of MAS is also suitable for discontinuous or complex surfaces.…”
Section: B Direct Problem Solution Using the Masmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach eliminates the singularity problems in radiation integrals. In the regularized form of MAS, Hankel's function (Green's function in 2D problems) is regularized and singularity problems are solved by regularizing the kernel of the radiation integrals (Hankel's function) [19]. For smooth surfaces, MAS gives better results, whereas the regularized form of MAS is also suitable for discontinuous or complex surfaces.…”
Section: B Direct Problem Solution Using the Masmentioning
confidence: 99%
“…In Table 1, dimensions regarding the geometry of the problem are provided. The electric field outside the object can be expressed as ( 7) [18,19]:…”
Section: B Direct Problem Solution Using the Masmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, a circular strip geometry excited by a cylindrical wave is investigated, with different impedance values on the outer and inner surfaces. The research examines resonant phenomena not observed in previous literature, demonstrating the influence of impedance values and location dependencies on the resonator structure's Q‐factor [26–28].…”
Section: Introductionmentioning
confidence: 99%